(3GdYdGbGJ GdYGeI hGdYdGbGJ GdGfSGfjI hGdQCj GdYGe eY OQGSI JWHjbjI ddYdGbGJ GdYGeI HCLgRI GdTQWI (B/s - (3GdHGR, Ydjs ((3GdGScfOQjI(B: s (3ecJHI heWHYI GdGTYGY GdafjI(B, s, 2002)
(3CgejI GdQCj GdYGe, hSGFd GdQGj GdYGe, hSGFd Jchjf GdQCj GdYGe hhSGFd bjGSg, GdQCj GdYGe hhSGFd GdGYdGe, GdYdGbGJ GdYGeI(B: (3GdYdGbGJ GdYGeI GdOGNdjI, GdYdGbGJ GdYGeI (B((3GdOGNdjI hGdNGQLjI(B) (3HLgGR GdTQWI, GdWHjYI GdeJejRI dYed GdTQWI hLeghQgG, hSGFd GJUGd GdTQWI HGdQCj GdYGes
Keywords: (3GdQCj GdYGes; (3GdTQWIs; (3GdYdGbGJ GdGfSGfjIs; (3GdYdGbGJ GdYGeIs